Effectiveness of Sealer Combination Zinc Oxide (ZnO) with Red Pine (Pinus densiflora) on Viscosity and Solubility (Laboratory Experimental) - Sukaton Sukaton; Latief Mooduto; Stheril Andani (Conservative Dentistry Journal, 2021)
Background: Failure of endodontic treatment is caused by 60% of poor obturation. Sealers have an important role in the obturation process, that is filling the root canals and the space between the dentin and the core material. Sealers must have low viscosity so that they can flow easily and fill the entire root canal space so can form a good seal and have physical properties that are not easily soluble to oral fluids to prevent sealer degradation which can cause gaps during filling and become a medium for bacterial proliferation. Red pine extract is a natural ingredient that contain flavonoid and phenolic acid that are effective in reducing the viscosity and solubility of the sealer combination ZnO with red pine. Purpose: To determine the effectiveness of sealer combination ZnO with red pine in reducing viscosity and solubility. Methods: Red pine (Pinus densilora) extract with a concentration of 100% was diluted to a concentration of 0.78% using the dilution formula M1.VI = M2.V2. Viscosity test was done by mixing ZnO with red pine extract 0.78% 1: 1 and calcium hydroxide (Ca(OH)2) with 1: 1 sterile aquadest as a comparison, then each sample was measured for viscosity using a brookfield viscometer. The solubility test was carried out by placing the paste on a disc with a diameter of 15 mm x 3 mm and then being set and immersed in distilled water for 24 hours then the percentage of solubility was calculated. Results: The viscosity value of combination ZnO with red pine is 19.89 Pa.s and the solubility is 0.0075%, while Ca(OH)2 with sterile aquadest had a viscosity of 23.32 Pa.s and a solubility is 0.029%. Conclusion: The combination of ZnO with red pine is effective in reducing the viscosity and solubility of the combination sealer. The viscosity and solubility of the combined sealer is lower than Ca(OH)2 with sterile aquadest.